Pathogenesis and management of fatigue in primary biliary cholangitis. Issue 1 (2nd January 2022) - Shamshtein, Dana; Liwinski, Timur
ABSTRACT: Background: Primary biliary cholangitis (PBC) is a cholestatic liver disease characterized by non-suppurative destructive cholangitis of the small intrahepatic bile ducts and female preponderance. Chronic fatigue, a condition marked by extreme tiredness and inability to function because of a lack of energy, is the most common symptom in PBC, affecting up to 80% of patients. However, the pathogenesis of PBC-associated fatigue is unknown, and treatment outcomes are poor. Purpose: We aim to provide an updated summary of pathogenesis and emerging treatments for fatigued PBC patients. Methods: We conducted a structured literature survey and compiled a narrative review. Results: Fatigue is often the most bothersome symptom in PBC patients and is frequently accompanied by cognitive impairment, depressive symptoms, and anxiety. Fatigue is an independent predictor of mortality in PBC. The pathophysiology of these phenomena is complex and poorly understood; therefore, a causal treatment is lacking. Multiple lines of evidence point towards biological, psychological, and social factors that are underlying and modulating the disease burden in fatigued PBC patients. Animal models suggest that an inflammatory liver-brain axis is implicated in the pathogenesis of cholestatic fatigue. The currently available management options for fatigue and cognitive symptoms are mainly supportive. However, specific medical treatment options for relieving fatigue symptoms emerge, including anti-inflammatory treatments. Conclusion: Emerging pathophysiological concepts and experimental therapies may improve outcomes of fatigued PBC patients in the near future.